Integrated visual culture in Neo-Chinese branding: A semiotic analysis of CHAGEE’s packaging and digital campaigns - Erlyana, Yana; Hidajat, Henny; Sutanti, Keisya Annabella (Universitas Indraprasta PGRI, 2026)
The